If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -83 = -79 Reorder the terms: -83 + y = -79 Solving -83 + y = -79 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '83' to each side of the equation. -83 + 83 + y = -79 + 83 Combine like terms: -83 + 83 = 0 0 + y = -79 + 83 y = -79 + 83 Combine like terms: -79 + 83 = 4 y = 4 Simplifying y = 4
| 14-18y=7y | | 6a-5a=9 | | -A+4=6 | | x+qsrt(x-9)=21 | | (5x^4)+(3x^2)+3=0 | | x+sqrt(x-9)=21 | | 2c+7=9 | | 8x-20=5x+7 | | 3u-6=0 | | 8sinx+5=1 | | y=-2+7*sin(4*x) | | 2*x+3=19 | | 0.625x+1875-x=0 | | 176/200 | | (9x-3)(-6x+7)=0 | | 2a-10=0 | | 7p-4=2p+11 | | 15^7x8^6/5^6x24^7 | | (2x+3)-2(5x-1)=(7x-1)-2(3x+1) | | 7x=(x-4)(x+6) | | 7-(1-3x)=9 | | 2z+3=5 | | (5x+5)2=20x+10 | | 2(4y-1)=-18 | | -6r-6r=12 | | 4x^5+x^3+2x+4=0 | | 3y+3=2-2y | | 4x^5+x^3+2x^2+4=0 | | 4(x+10)+2(3x+20)=180 | | 5a-17=35 | | 5(3-c)=5c+3 | | (4/x)=(2/3) |